GA document 117 : international 2011, emerging future. (Tokyo : A.D.A. edita, 2011)
- Aires Mateus: Parque de los Cuentos, Malaga, Spain##- ALEJANDRO ARAVENA: Anacleto Angelini Innovation Center, Campus San Joaqui Pontificia, Universidad Catolica, Santiago, Chile##- BIG/BJARKE INGELS: Amagerforbraending - New Waste Treatment Plant, Copenhagen, Denmark##- Sou Fujimoto: 'Cloud' Arena, Las Torres de Cotillas, Spain##- Kengo Kuma: V&A at Dundee, Dundee, Scotland, U.K.##- Michael Maltzan: Mashouf Performing Arts Center, San Francisco State University, San Francisco, California, U.S.A.##- MVRDV: China Comic and Animation Museum, Hangzhou, Hangzhou, Zhejiang, China##- Hrvoje Njiric: Park B - New University Campus in Zagreb, Zagreb, Croatia##- O'Donnell + Tuomey: London School of Economics New Students' Centre, London, U.K.##- Fernando Romero :Doha Gallery, Doha, Qatar##- SANAA: J Project, Okayama, Japan##- Selgascano: WH.K - Penal Court Building, Madrid, Spain##- Snohetta: in collaboration with Zeidler Partnership, Ryerson University Student Learning Centre , Toronto, Ontario, Canada##- SPBR Arquitetos: Treetech Headquarters, Atibaia, Sao Paulo, Brazil##- Anton Garcia-Abril: WoHo##- Thomas Heatherwick: Teesside Power Station, Teesside, near Middlesbrough, U.K.##- Christian Kerez: Museum of Modern Art, Warsaw, Warsaw, Poland##- Smiljan Radic: Yungay, Santiago, Chile##- RCR Arquitectes: Soulages Museum and Ordination of the Park of 'Foirail', Rodez, France##- Michel Rojkind: R432, Reforma, Mexico City, Mexico##- Wolfgang Tschapeller: Centre for Promotion of Science, Belgrade, Belgrade, Serbia##- UNStudio: Raffles City Hangzhou, Hangzhou, Zhejiang, China##- Wang Shu: Shi Li Hong Zhuang Museum, Ninghai, Zhejiang, China
boek